1994
DOI: 10.1203/00006450-199401000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nucleotides Influence Lipoprotein Metabolism in Newborn Infants

Abstract: ABSTRACT. Nucleotide supplementation of adapted-milk formulas may be of interest for infant nutrition because nucleotides are involved in the synthesis of proteins and other macromolecules such as phospholipids, and thereby facilitate lipoprotein synthesis. To determine whether dietary nucleotides influence plasma lipoproteins in newborns, we have studied the plasma-lipoprotein concentrations and the composition of the major lipoprotein fractions during the first week of life in two groups of preterm infants f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 12 publications
1
26
1
Order By: Relevance
“…Dietary nucleotides are known to play many biochemical and physiological roles, serving as precursors for nucleic acid synthesis, being involved in protein synthesis and influencing lipid and lipoprotein metabolism (24)(25)(26). Recently, we found that the levels of plasma apolipoprotein A-IV, which is of intestinal origin, was increased by dietary nucleotide supplementation in newborn infants (Pediatr.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary nucleotides are known to play many biochemical and physiological roles, serving as precursors for nucleic acid synthesis, being involved in protein synthesis and influencing lipid and lipoprotein metabolism (24)(25)(26). Recently, we found that the levels of plasma apolipoprotein A-IV, which is of intestinal origin, was increased by dietary nucleotide supplementation in newborn infants (Pediatr.…”
Section: Resultsmentioning
confidence: 99%
“…During the last decade, it has been indicated that dietary nucleotides may play some physiologically important role especially in infants (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In addition to nucleotides, it has been recently suggested that dietary nucleosides may also participate in the differentiation of intestinal cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…It should be a great load for infants. Also some physiological roles of dietary nucleotides have been reported (2)(3)(4)(5)(6)(7)(8)(9)(10). So, it is quite reasonable to provide infant nucleotide and/or nucleoside from milk.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of dietary nucleotides on the gastrointestinal system and on hepatic growth and function have only been observed in animal studies (Uauy et al 1990;Bustamante et al 1994;Novak et al 1994). Nucleotide supplementation appeared significantly to increase all plasma lipoprotein concentrations in preterm, but not in term infants (Sanchez-Pozo et al 1994). A quite fascinating finding that warrants further study has been that dietary nucleotides increased indices of cell mediated immunity in infants without, however, influencing incidence and severity of infections (Carver et al 1991).…”
Section: N U C L E O T I D E Smentioning
confidence: 99%